Evaluasi Kebijakan Pembangunan Jalur Luar Lingkar Barat dalam Meningkatkan Konektivitas Antar Wilayah di Surabaya - Meriana Yumame; Sapto Pramono; Ika Devy Pramudiana; Sri Roekminiati (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The development of the Western Outer Ring Road (WORR) in Surabaya is a solution initiated to address the worsening traffic congestion caused by the imbalance between the number of vehicles and the limited road length. This study aims to evaluate the impact of JLBB development on inter-regional connectivity and traffic congestion reduction. The research uses a qualitative approach with a case study method through document analysis and interviews with relevant stakeholders. The findings indicate that the planned 19.8 km JLBB is expected to reduce congestion in the city center, improve accessibility, and strengthen connectivity between Surabaya and surrounding cities such as Sidoarjo and Gresik. The project also has the potential to support economic growth through improved goods distribution and create job opportunities around the corridor area. However, the implementation of this project faces challenges in land acquisition and budget constraints, which hinder the acceleration of development. Therefore, regular evaluations and further coordination between the city government and the private sector are necessary to address these obstacles. The JLBB development is expected to make a significant contribution to smooth mobility, reduce traffic congestion, and enhance the economy of Surabaya in the long term.